IDIOM ESTETIKA POSTMODERNISME DALAM BUKU KUMPULAN PUISI “HOMPIMPA ALAIUM GAMBRENG” KARYA HAMZAH MUHAMMAD - Muhamad Nafidz Firdzani; Rahmayanti, Indah (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2025)
This study investigates the application of postmodern aesthetic idioms in literary works, with a focus on the poetry collection “Hompimpa Alaium Gambreng” by Hamzah Muhammad. The research employs the theoretical framework of postmodernism as proposed by Wijayati and literary postmodernism as articulated by Endraswara. Utilizing a qualitative descriptive method, data were collected through observation and note-taking techniques and analyzed descriptively. The findings indicate that all five idioms of postmodern aesthetics are manifested in the poems. These idioms contribute to the creation of poetry that engages more directly with social realities through a light and accessible narrative style. By subverting conventional literary norms, this approach enables broader imaginative expression and offers an alternative medium for representing social realities. Consequently, the work becomes more inclusive and accessible to a wider audience across various social backgrounds.